"I'll Take Two Please … Sike": Paying the Black Tax in Adult Education. Issue 2 (May 2022) - Gnanadass, Edith; Privott, Daryl R.; Ramdeholl, Dianne; Merriweather, Lisa R.
We live in a society wherein anti-Black racism is pervasive. It infiltrates every aspect of life, including work life spaces. In spite of the recent call for higher education to become antiracist, a tall order for an institution literally and figuratively built on racist attitudes and behaviors, higher education continues to be a cesspool for racism. Literature is replete with stories of the toll working in such environments takes on Black and Brown people. Some have called it "The Black Tax." Palmer and Walker (2020) riff off of Rochester's (2018) popularization of the financial "Black Tax" to relate it to psycho-social realities of Black people. Palmer and Walker define it as "the psychological weight or stressor that Black people experience from consciously or unconsciously thinking about how White Americans perceive the social construct of Blackness" (para. 2). Black and Brown adult educators pay this tax multiple times in the course of working in academe and that tax is doubled when they teach subjects that center equity and social justice. This paper will share through dialogic reconstruction multivocal layered accounts of Black and Brown adult educators, each with a different positionality, but all who understand what it means to pay the Black tax in adult education. Working from a critical race lens, the authors engage in a collaborative evocative autoethnography to analyze their experiences with the impact of the Black tax on their role as adult education professors in higher education. We determined the following themes as salient to our Black Tax experience: A sick place, moving the line, bring me a rock, and weaponizing our power. Understanding how anti-Black racism operates is key to adult education as a discipline moving toward its ever-elusive goal of parity and justice and reflecting on its theories and practices that stymie those efforts.